THE DYNAMICS OF INTERPERSONAL COMMUNICATION IN PEER GROUPS AT SDIT PLUS USMAN BIN ALI MEDAN - Vivi Nabilla; Suryani Hardjo; Siti Aisyah (International Journal of Cultural and Social Science, 2026)
This study aims to explore the dynamics of interpersonal communication within peer groups and the meaning of communication experiences among elementary school students. The research problem emerged from preliminary observations and interviews indicating dominance in group discussions, unequal participation, and conflicts arising from verbal and nonverbal misunderstandings in the school environment. This study employed a qualitative approach with a phenomenological design. The participants consisted of nine respondents: four students, four parents, and one homeroom teacher at SDIT Plus Usman Bin Ali Medan. Data were collected through observations and in-depth interviews and analyzed using data reduction, data display, and conclusion drawing, supported by triangulation to ensure credibility. The findings reveal that students’ interpersonal communication manifests in cooperative, competitive, and conflictual patterns. Children interpret communication as experiences of acceptance or rejection, which influence their self-confidence and social relationships. The main themes identified include openness, empathy, supportiveness, equality, and conflict management. The study implies that schools should strengthen communication and socio-emotional skill development programs to foster a supportive and psychologically safe interaction environment.